Analysis of the Use of Educational Game Media for Science Subjects on Digestive System Material - Safrudin Wahyu Jadmiko; Deni Setiawan (Postgraduate, University of Mataram, 2024)
Educational games are games that are used in the learning process, as a form of technology adaptation in the world of education to help teachers improve the learning process in the classroom. Researchers conducted research with the aim of analyzing the use of educational game media during learning; analyze the impact of using educational game media; how important educational game media is in class V science and science learning at Japeledok State Elementary School. This research uses descriptive qualitative research methods. This research was carried out at SDN Japeledok, Pancur District, Rembang Regency. SDN Japeledok has a total of 11 class V students consisting of 7 boys and 4 girls. The data taken from this research are observations, questionnaires, interviews and documentation using triangulation techniques. The results obtained from this research are the use of educational game media in Japeledok Elementary School that have been implemented by class teachers are Wordwall and Quizizz; The impact given after implementing educational game media is an interactive and fun learning experience, training students' thinking skills, increasing interest and motivation to learn, and making students more active in the learning process in class. Overall, educational games have had a lot of positive impacts on students and teachers. Judging from the impact this educational game has, it has an important role in implementing learning. Educational game media not only provides an interesting alternative in education, but also opens up new opportunities to improve the quality of learning and learning experiences for various types of learners.